2001
DOI: 10.1038/sj.bjp.0704087
|View full text |Cite
|
Sign up to set email alerts
|

CXC chemokines, MIP‐2 and KC, induce P‐selectin‐dependent neutrophil rolling and extravascular migration in vivo

Abstract: 1 The purpose of this study was to examine the impact of CXC chemokines, i.e. macrophage in¯ammatory protein-2 (MIP-2) and KC, on leukocyte-endothelium interactions in detail and to evaluate the role of P-selectin by use of intravital microscopy in the mouse cremaster muscle. 2 Administration of MIP-2 and KC provoked a dose (5 ± 500 ng)-and time (0 ± 4 h)-dependent increase in leukocyte rolling, adhesion and tissue recruitment. Neutrophils comprised more than 92% of the leukocyte response. Pretreatment with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 52 publications
7
92
0
3
Order By: Relevance
“…Other authors have also demonstrated that both MIP-2 and KC were produced in a delayed-type hypersensitivity (DTH) model, but only neutralizing antibodies against MIP-2 were able to reduce neutrophil accumulation and suppress the DTH reaction [24]. MIP-2 and other CXC-ELR + chemokines bind with high affinity to both CXCR1 and CXCR2 expressed on several cell types including T lymphocytes, NK cells, neutrophils, eosinophils, basophils, dendritic cells and platelets [25][26][27]. Whereas human neutrophils express both CXCR1 and CXCR2, only CXCR2 has been detected in mice [8,9,23,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also demonstrated that both MIP-2 and KC were produced in a delayed-type hypersensitivity (DTH) model, but only neutralizing antibodies against MIP-2 were able to reduce neutrophil accumulation and suppress the DTH reaction [24]. MIP-2 and other CXC-ELR + chemokines bind with high affinity to both CXCR1 and CXCR2 expressed on several cell types including T lymphocytes, NK cells, neutrophils, eosinophils, basophils, dendritic cells and platelets [25][26][27]. Whereas human neutrophils express both CXCR1 and CXCR2, only CXCR2 has been detected in mice [8,9,23,28].…”
Section: Discussionmentioning
confidence: 99%
“…CXCR2 mRNA expression in peritoneal cells from antigen (OVA)-challenged immunized mice were detected by RT-PCR, based on a previously described protocol [25,40]. Total cellular RNA from 1-h antigen-challenged peritoneal cells was extracted using the Trizol reagent (Gibco BRL, Life Technologies, Rockville, MD) according to the directions supplied by the manufacturer.…”
Section: Rna Extraction and Rt-pcr Analysismentioning
confidence: 99%
“…23 Like IL-8, P-selectin is presynthesized and stored in endothelial cell Weibel-Palade bodies 14 and is rapidly mobilized to the cell surface after exposure to Ang II. 15 Because CXC chemokines induce P-selectin upregulation, 24 it is possible that the release of IL-8 in response to Ang II augments the P-selectin upregulation. Therefore, in addition to their role in Ang II-induced neutrophil adhesion and migration, CXC chemokines may also contribute to the rolling response elicited by this peptide hormone.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be important for CXC chemokines to create a concentration difference between two compartments, which is necessary for mobilization of neutrophil migration. CXC chemokines have been implicated in all steps in the extravasation process of leukocytes, including rolling, adhesion, and transmigration in vivo (27). Thus, the role of blood CXC chemokines may primarily focus on the activation of neutrophils and endothelial cells, setting the stage for neutrophil migration, whereas the local CXC chemokines chiefly function chemotactically during sepsis.…”
Section: Discussionmentioning
confidence: 99%